Fifty years of environmental changes of the Amacuzac riparian ecosystem: a social perceptions and historical ecology approach - Eufracio-Torres, Angel E.; Wehncke, Elisabet V.; Lopez-Medellin, Xavier; Maldonado-Almanza, Belinda (Ethnobiology and Conservation, 2016)
Critical aspects of hydrological science need to include historical perspectives about land and water use, and to understand the kind of knowledge policymakers and society require, so that this expertise can be translated into actions directed to water management challenges. We combined environmental perceptions with historical ecology techniques to understand the past and present relationships between people and the riparian environment, and to highlight the overriding influences of historic landuse changes in the region. We analyzed the perceptions of elderly stakeholders who have lived for >50 years in ten localities established inside and outside a protected area along the Amacuzac, one of the largest rivers in Morelos, Mexico. The river was and still is an important part of community life, in spite of its present poor condition. Perspectives of elders living inside the protected area were mostly related to conservation aspects of ecosystem functioning, impact on vegetation, and water problems related to land use. The loss of biodiversity and ecosystem services were recognized as the leading cause ofthe loss of ecosystem products and of their commercialization, as well as other changes in local economies. We conclude that effectively protected areas can improve the biological quality of watercourses if a decidedly more conservationist focus is placed upon streams and the surrounding territory.